Farmers adjustments to rice production in response to flood hazard in Haor basin areas of Bangladesh - Nahar, Jakia Quamrun (BRAC University, 2017)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Master in Disaster Management, 2016.